The state component and civil borders in defining the boundaries and structure of church-administrative jurisdiction on the example of the Galician metropolitanate of the XIV century - archpriest Volodymyr Vakin (Волинський благовісник, 2020)
When the independence of the Ukrainian state was proclaimed in 1991, the issue of the canonical independence of the Ukrainian Orthodox Church with its administrative church center in Kyiv was obvious to arise. Representatives of the Russian Orthodox Church began to oppose this idea, arguing for a monopoly on “canonical territory” and a spiritual ternary union that transcends any state borders. Thus, by manipulating terms and distorting the true ecclesiological doctrine of the Orthodox Church about its structure and supreme ecclesiastical authority, the holy hierarchs of the ROC created and still encourage divisions in Ukrainian society on cultural, linguistic and ecclesiastical grounds. This situation clearly shows the vital importance of a proper understanding of the doctrine of the dimension of a single Orthodox Church and, at the same time, the local nature of its spiritual mission within clearly defined autocephalous jurisdictions. The position of ROC leaders could be justified in the Roman Catholic environment, where the doctrine of the earthly structure of the Church really dominates the position of a single administrative spiritual center headed by the Pope over other church-administrative units of the entire Roman Catholic Church. Since the Moscow Patriarchate positions its affiliation with Orthodoxy, there is a natural cognitive dissonance in the statements calling for adherence to the canonical rules and procedures of Orthodox ecclesiology in resolving the Ukrainian church issue and, at the same time, denying the possibility of the existence of local Orthodox Church in Ukraine. Moreover, the accusation against the Ukrainian state of “interfering” in the life of the Orthodox Church of Ukraine seems controversial in the context of receiving Tomos about the independence of an autonomous church and simultaneously the active alliance of the ROC with the state bodies of the Russian Federation looks weird in implementing the Russian imperial political project within the sovereign countries of Russia, Ukraine and Belarus. To demonstrate the practical expression of legal ecclesiastical theory in the field of this issue, as well as to confirm the historical longevity of the autocephaly of the Orthodox Church of Ukraine, the examples of the discovery of the Galician metropolitanate in the XIV century have been used in the article. The relevance of these historical precedents has been highlighted by the fact that it was in the fourteenth century that the borders of the principalities changed dynamically and, accordingly, secular leaders, motivated by the state position to prevent destructive influences of external forces, persistently sought to have their own church autonomous system, which was reflected in authentic sources of both ecclesiastical and civil origin. We propose to divide this study into two sections. In the first part we consider the theological and canonical understanding of this issue in the context of the preconditions for the creation of a separate Galician metropolitanate in the early fourteenth century.